DEIKSIS SOSIAL PADA CERPEN REMBULAN DI MATA IBU KARYA ASMA NADIA - Safira Salsabila; Mira Fitri Yani; Bambang Riadi; Rahmat Prayogi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
The result of a writer's creativity in expressing their imagination, ideas, and feelings to describe the reality of life around them is often referred to as literature. One form of literature that is concise yet rich in meaning is the short story. This study aims to describe the form and function of social deictics used by Asma Nadia in her short story Rembulan di Mata Ibu (The Moon in Mother's Eyes). The approach used is descriptive qualitative with the steps of reading the text in depth, recording relevant data, analyzing the linguistic context, and interpreting the social meaning of the characters' speech. The results show that there are six types of social deictics covering the aspects of gender, age, education, profession, greetings, and nicknames. Each form shows differences in social status and relationships between participants in society. These findings confirm that the use of social deictics not only functions as linguistic markers but also as a reflection of the social and cultural values that exist in society. The uniqueness of this study lies in its in-depth analysis of social relationships in Asma Nadia's short stories, which were examined from a stylistic and pragmatic perspective.